Climate related societal consequences and responses during the 19th century, South Africa and Lesotho, 1830-1900 - (Rampath) Beharie, Shantal (My University, 2019)
Documentary evidence and established chronologies for southern Africa contain rich sources of information on social and environmental impacts and consequences on past societies in southern Africa. The primary aim of this research is to use such established chronologies to determine the environmental and social consequences and relevant responses that followed such droughts and floods including ENSO years where possible. All relevant information was extracted from existing research as well as original data that had already been collected for such regions. The data used for this study involved collecting historical records from the various regions that reflected social and environmental consequences and responses from published historical projects. Such published projects contained 19th century climatic chronologies that were already established from raw primary data such as newspapers, journals, diaries, newsletters and government annual reports in order to make relevant associations between climatic events, societal impacts, consequences and responses. All qualitative data for impacts and consequences were also converted into quantitative data. The outcomes of the study revealed that the impact of droughts had a major impact towards livelihoods and resource availability for southern Africa. In comparing adaptive capacity across the regions, the data revealed that KwaZulu-Natal may have taken longer to recover from most of the impacts, while regions such as Namaqualand and Lesotho were shown to have shorter impact periods and quicker recovery times for certain impacts such as poverty and famines. Qualitative data also showed that various responses were undertaken to cope with such impacts. Coping mechanisms which included religious responses, such as rainmaking and prayer for rains were common throughout Lesotho and KwaZulu-Natal, while migration and transhumance practices were common the coping mechanisms in Namaqualand during droughts and resource shortages in the 19th century.
A dissertation submitted to the Faculty of Science in fulfilment of the requirements for the degree Master of Science 29 May 2019, Johannesburg
Keywords: Geochronometry; Geology